Lhasa. La route chante - De Sela, Lhasa (Éditions Textuel, 2008)
La chanteuse mexicano-américaine Lhasa de Sela, également passionnée par la peinture, le dessin, la photographie et l'écriture, retrace son parcours et dévoile les lectures, les artistes et les pensées qui la nourrissent (Jung, Hugo, Géricault, Cat Stevens, etc). En 1998, la chanson la Llorona la fait connaître en Europe et au Québec.

Three Canadian Sephardic Women and their Transplanted Repertories: From Salonica, Larache and Sarajevo to Montreal and Kahanawá:ke - Cohen, Judith R. (Folk Music, Traditional Music, Ethnomusicology: Canadian Perspectives Past and Present, 2007)

The Ladino Song in the 20th Century: A Study of the Collections of Emily Sene and Bouena Sarfatty-Garfinkle - Havassy, Rivka (Université Bar-Ilan, 2007)
Keywords: Pas de lien web

La rencontre des musiques du Moyen-Orient et de l'Occident : esthétisme, composition et analyse - Makdissi-Warren, Katia (Université de Montréal, 2007)
The object of this dissertation is the meeting of Middle-Eastern and Western music. The dissertation includes an essay and seven original compositions (scores and recordings). The text begins with the exposition of the basics of Middle-Eastern music required to understand my artistic approach. The 'taqasim', a major musical form in the Middle-East and a source of inspiration for my work is presented in more detail. The second chapter deals with the philosophy of aesthetics involved in the intermixing of musical cultures. Concerns about the coherence of commingled languages are exposed. The concepts of intermixing, cultural identity and coherence of a work are submitted for discussion. For a given work, does the notion of coherence retain its essence from one person to the next according to culture and social context? This questioning is directly linked to the creation and generation of the processes of development for the musical material in my compositions. Throughout the chapter, I position my approach in relation to the thinking of authors such as Adorno, but also relative to personal experiences. In chapter 3 I describe the writing processes I have developped in order to create a sound fabric wherein Middle-Eastern music meets that of the West. My work defines processes for treating parameters in order to draw together elements of both Eastern and Western musical expressions into a distinctive language <f> <fr><nu>.</nu><de>7</de></fr></f> the key to this is grasping how one musical element influences another. Using analysis as a starting point for the comparison of musical parameters in each of the languages, I have elaborated new commingling (intermixing) techniques. This chapter is therefore devoted to the cross-relational writing techniques that have been evolved to adequately support my artistic approach. The final chapters of this dissertation feature the detailed analyses of three of my compositions: 'Jet Stream, Algorythme and PLB'. Each piece's form, sections and sub-sections are presented followed by the analysis of its basic musical material and development.

Répertoire musiques du monde à Montréal - Laurent, Sophie; Bélanger, Thomas (Conseil des arts de Montréal, 2005)

The Memoirs of a Partisan from Salonika - Melammed, Renee Levine (Nashim: A Journal of Jewish Women's Studies & Gender Issues, 2004)